2016
DOI: 10.1007/s00606-016-1297-3
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between two self-compatible cytotypes of Herbertia lahue (Iridaceae): evidence from genotypic and phenotypic variation

Abstract: The polyploid species Herbertia lahue (Molina) Goldblatt is widespread in the grassland areas of southern America. In this study, genotypic and phenotypic variations among hexaploids and octoploids from H. lahue were assessed based on quantitative floral traits and ISSR markers. Additionally, gynoecium and breeding systems were analysed through anatomical analysis and hand-pollination experiments. Cytotypes are self-compatible, and the anatomy of the embryo sac remains similar in hexaploids and octoploids. AMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 58 publications
(109 reference statements)
1
13
0
Order By: Relevance
“…Although the global F ST values point to more structured populations, which is consistent with other species of Iridaceae ( Hannan and Orick, 2000 ; Wróblewska et al , 2003 ; Wang et al , 2009 ; Tacuatiá et al , 2012a ; Stiehl-Alves et al , 2016 , 2017 ), the pairwise comparison of F ST revealed that some populations are less differentiated from each other ( F ST < 0.20) and retain residual gene flow among them ( N m > 1) ( Table 5 ). The population genetic structure in plants reflects the interaction of many evolutionary processes, including habitat fragmentation and population isolation, mutation, genetic drift, mating system, gene flow, and selection ( Hamrick and Godt, 1996 ; Hannan and Orick, 2000 ; Nybom and Bartish, 2000 ; Nybom, 2004 ; Stiehl-Alves et al , 2016 ). In this sense, although the STRUCTURE analysis detected two genetic clusters for the molecular dataset ( Figure 2 ), consistent with the UPGMA dendrogram ( Figure 3 ), the estimates of pairwise gene flow support the result of the STRUCTURAMA analysis ( K = 1), since gene flow was detected even for the most differentiated populations (ESC218 and ESC661).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Although the global F ST values point to more structured populations, which is consistent with other species of Iridaceae ( Hannan and Orick, 2000 ; Wróblewska et al , 2003 ; Wang et al , 2009 ; Tacuatiá et al , 2012a ; Stiehl-Alves et al , 2016 , 2017 ), the pairwise comparison of F ST revealed that some populations are less differentiated from each other ( F ST < 0.20) and retain residual gene flow among them ( N m > 1) ( Table 5 ). The population genetic structure in plants reflects the interaction of many evolutionary processes, including habitat fragmentation and population isolation, mutation, genetic drift, mating system, gene flow, and selection ( Hamrick and Godt, 1996 ; Hannan and Orick, 2000 ; Nybom and Bartish, 2000 ; Nybom, 2004 ; Stiehl-Alves et al , 2016 ). In this sense, although the STRUCTURE analysis detected two genetic clusters for the molecular dataset ( Figure 2 ), consistent with the UPGMA dendrogram ( Figure 3 ), the estimates of pairwise gene flow support the result of the STRUCTURAMA analysis ( K = 1), since gene flow was detected even for the most differentiated populations (ESC218 and ESC661).…”
Section: Discussionsupporting
confidence: 78%
“…As revealed by ISSR, C. crocoides has a relatively high genetic diversity at the species level ( Table 3 ) compared to other herbaceous or endemic species ( Hamrick and Godt 1990 ; Nybom and Bartish, 2000 ; Nybom, 2004 ). High levels of genetic diversity were also detected for other native species from South American grasslands ( Jakob et al , 2009 ; Lorenz-Lemke et al , 2006 , 2010 ; Sede et al , 2012 ; Fregonezi et al , 2013 ; Turchetto et al , 2014 ; 2016 ; Barros et al , 2015 ; Stiehl-Alves et al , 2017 ), some of these being species with restricted geographical distribution ( Lorenz-Lemke et al , 2006 , 2010 ). At the population level, AMOVA ( Table 4 ) showed that most of the genetic variation was found within populations, suggesting a genetic structure characteristic of outcrossing plants ( Nybom and Bartish, 2000 ; Nybom, 2004 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Polyploid cytotypes have been reported in some Iridaceae species, such as S. micranthum (4 x and 6 x ; Tacuatiá et al , 2012 ), S. sellowianum Klatt (4 x ; Fachinetto et al , 2018 ) and Herbertia lahue (Molina) Goldblatt (4 x , 6 x and 8 x ; Moraes et al , 2015 ; Stiehl-Alves et al , 2016 ). However, in this study we did not find any cytotypes within taxa.…”
Section: Discussionmentioning
confidence: 99%